Sport During the Ramadan Fasting Period: Health Benefits and Risks and Recommendations for Practicing - Said, Ihbour (International Journal of Sport Studies for Health, 2023)
Context: The subject of "Sport During Ramadan" focuses on the impact of fasting during the holy month of Ramadan on athletic performance and physical activity. Muslims around the world fast from sunrise to sunset during this month, abstaining from food, drink, and other physical needs. Our hypothesis suggests that during Ramadan, the fasting period can cause particular problems for athletes and people involved in sports and physical activities that require a lot of stamina and energy.Evidence Acquisition: A systematic review of the literature was conducted using the search equation "sport during Ramadan" in the PsycInfo, PubMed and ScienceDirect databases, in order to identify the 40 articles on the subject up to the year 2022.Results: Taking into account the similarities of the contents of the 40 targeted articles, 24 articles were selected. During the fasting period of the month of Ramadan, engaging in sports and exercise during Ramadan can have numerous benefits for physical and mental health. However, physical activities that require a lot of endurance and energy can pose physical health risks, including dehydration, hypoglycemia, muscle cramps, fatigue and delayed recovery.Conclusions: Participating in sports and exercise during Ramadan can have many benefits for physical and mental health, as well as spiritual awareness and community engagement. During this time, uncontrolled physical exertion can have detrimental effects on health. Proper hydration combined with a rich and balanced diet during the non-fasting period and quality sleep can help overcome the risks associated with exercising during Ramadan. It is important that Muslims prioritize their health and well-being during this time and consult a physician if necessary before engaging in physical activity.